Proposed Go-to-Market Strategy for new mobile Application on leisure industry in indonesia - Analyes Perdana, M Jumeidil; Rahardjo, Budi (The Indonesian Journal of Business Administration, 2016)
Abstract— Indonesia is a mobile-first country where majority access the internet through mobile gadgets such as smartphone or tablet. The number of internet users in Indonesia is 88 million and continue raising. The momentum has given impact to the national trend which is called the digital economy. People in Indonesia also has seen the emergence of national sharing platforms such as Go-Jek, a startup that let us sharing the motorbike in Indonesia, as well as the concept of sharing economy startups such as Grab, Uber, and Airbnb. In Indonesia, experience economy is also raising, especially for millennials or young generation. The number of an event such as music concert, sports entertainment, and other experience or event, gradually increase year by year. According to McKinsey data in 2011, the leisure industry is expected to growth 7.5% annually. Based on the current trend such as sharing economy, digital economy, and experience economy among the young generation, a startup company, Pleasurra is taking action to innovate on leisure industry business by combining the sharing economy with experience economy through technology especially mobile application. However, Pleasurra is facing several problem in their business especially getting traction of users in their mobile application. The problem can result. In this journal, the writer will focus on marketing problem of Pleasurra. The business condition will be analyzed first by using 5’C analysis including climate, customers, company, competitors, and collaborators. After conducting the root cause analysis, the main problem is low traction of users. In order solve that, the writer propose to define go-to-market strategy. The go-to-market strategy will be proposed based on the 3V’S marketing mix model by Nirmalya Kumar. Valued customers, value proposition, and value of network. The supporting solutions such as word of mouth marketing and content marketing also will be explored further in this journal. In the end, the writer will get the right go-to-market strategy for Pleasurra mobile application. Keywords: digital economy, leisure industry, startup marketing, go-to-market, 3v’s model